Why would an ethically proven Shockvertising campaign backfire so aggressively? Ethics boundaries in advertising and audience’s perspective case study: Spinneys “missing” advertising campaign Lebanon 2025 - Khoury, Josiane El (International Journal of Innovative Research and Scientific Studies, 2025)
In advertising campaigns, particularly billboards, brands resort to using attention-grabbing techniques to capture the audience’s focus and manipulate consumer behavior. Multiple categories can also be employed to convey a message within a single campaign. These categories range from shock advertising, engagement advertising, teaser advertising, reveal advertising, and many others. This is precisely what the Spinneys campaign tended to achieve in announcing its new branch, employing these advertising techniques. This campaign initiated a wave of discontent on social media and in society. That wave quickly turned aggressive, bombarding the campaign with criticism. Many argued that, in a country already facing war and uncertainty, a commercial campaign that plays on the theme of “missing people” could feel harmful and trigger deep fear among citizens. However, the ethical boundaries of these advertising categories vary according to several factors, such as the audience’s psychology and background, as well as the manner in which the campaign is executed, including its visuals, language, and other elements. The findings of this study highlight the ethical boundaries of these types of advertising, as well as how to maintain responsibility toward society while achieving creativity and leaving an impact.